2017
DOI: 10.1186/s13063-017-2328-2
|View full text |Cite
|
Sign up to set email alerts
|

Does motivation matter in upper-limb rehabilitation after stroke? ArmeoSenso-Reward: study protocol for a randomized controlled trial

Abstract: BackgroundFifty percent of all stroke survivors remain with functional impairments of their upper limb. While there is a need to improve the effectiveness of rehabilitative training, so far no new training approach has proven to be clearly superior to conventional therapy. As training with rewarding feedback has been shown to improve motor learning in humans, it is hypothesized that rehabilitative arm training could be enhanced by rewarding feedback. In this paper, we propose a trial protocol investigating rew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 37 publications
0
24
0
1
Order By: Relevance
“…BCI-based training can be considered a type of motor learning to modify neuronal activities through sustained feedback and reward. Studies have identified feedback and reward as important contributors to neurorehabilitation (34)(35)(36)(37). However, the relationship between BCI training and feedback/rewardrelated regions of the brain has not been extensively investigated; thus, the efficacy and mechanisms of BCI-based training remain unclear, such as the effects on subacute stroke patients, alterations to sensorimotor area-related networks, and precise relationships with UL function.…”
Section: Introductionmentioning
confidence: 99%
“…BCI-based training can be considered a type of motor learning to modify neuronal activities through sustained feedback and reward. Studies have identified feedback and reward as important contributors to neurorehabilitation (34)(35)(36)(37). However, the relationship between BCI training and feedback/rewardrelated regions of the brain has not been extensively investigated; thus, the efficacy and mechanisms of BCI-based training remain unclear, such as the effects on subacute stroke patients, alterations to sensorimotor area-related networks, and precise relationships with UL function.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, positive patients’ motivation requires an encouraging environment and good interaction between the therapists and the patients. Some other studies also suggested that training devices which can provide rewarding schemes in a gaming environment had the ability to enhance the motivation of patients [ 44 , 45 ]. However, how to optimally apply motivational therapy into the rehabilitation to achieve better training outcomes is still unclear and need to be further investigated [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ArmeoSenso system [31,32,33,34] is an upper limb rehabilitation platform for the home environment. It consists of a motion capture system based on the wearable sensors which are presented in this paper, a PC with a large screen for visual feedback and touch input, as well as a therapy gaming software (implemented in Unity3D, Unity Technologies Inc., San Francisco, USA).…”
Section: Methodsmentioning
confidence: 99%
“…A simple, rule-based classifier is used to detect whenever the user has returned to this rest pose and then the drift is corrected using the magnetometer. This tracking method is implemented in ArmeoSenso [31,32,33] (Figure 1), a VR home therapy system for upper-limb rehabilitation after neurological injury (a video demonstration of the system can be found online [34]). We present the tracking method and validate its long term accuracy and latency.…”
Section: Introductionmentioning
confidence: 99%